Biodiversity in environmental assessment : enhancing ecosystem services for human well-being - Slootweg, Roel (Ecology, biodiversity, and conservation, 2010)
"Human induced development activities are introduced with insufficient attention to their consequences for our living environment, even in cases where environmental assessments have been carried out. This apparent lack of attention to biodiversity in environmental assessment is rooted in the difficulties we have in adequately addressing biodiversity within the scope, time frame and budget allocated for assessments. This book provides a conceptual background and practical approaches to overcome these difficulties. It integrates the objectives of the Convention on Biological Diversity, its ecosystem approach, and the conceptual framework of the Millennium Ecosystem Assessment into a comprehensive approach to biodiversity in environmental assessment. It highlights the need to consider the value of biodiversity based on its use by each stakeholder, addresses the importance of both social and economic development to reach the Millennium Development Goals, and provides insights into ways to balance present and future needs"--Provided by publisher.